Еxploring frugal innovation’s contribution on the manufacturing companies: an in-depth systematic review - Morelos Gómez, José; Vargas Franco, Diana; Romero Sánchez, Gisselle (Serbian Journal of Management, 2023)
In this paper, a systematic review of the literature was carried out in order to identify the contributions of frugal innovation in the manufacturing sector. The above, with the objective of knowing these innovations, highlighting the relevance and its contribution to this sector within the global emerging markets. The PRISMA method was used to perform meta-analysis of the theoretical, scientific and practical contributions of goods and services resulting from the frugal philosophy in the emerging manufacturing sector. To achieve the objectives of this research, three indexed databases of high scientific quality and visibility were considered: Scopus, Ebscohost and Science Direct in the period 2010-2020, with a search equation defined by keywords and exclusion and inclusion criteria, in which a first search of 15079 articles was obtained. As a result of the final filtering process, 52 documents were obtained that allowed the identification of these innovations, their classification, description, frugal, social and economic contribution in the benefited communities. This paper provides relevant findings related to the contribution of future perspectives of similar studies and empirical evidence of frugal operational processes (products) that drive the competitiveness of manufacturing firms.
Keywords: frugality; innovation; emerging markets; manufacturing sector